The characteristics of strike-slip faults and their control on hydrocarbon distribution in deep carbonate reservoirs of the central Sichuan Basin - Liang, Shangzi; Li, Zhong; Zhang, Wang; Gao, Yang (Frontiers in Earth Science, 2023)
The past decade has witnessed a breakthrough in the gas exploration of deep marine carbonates of the Sichuan Basin. Namely, the discovery of commercial hydrocarbon reservoirs in the Dengying (Sinian) and Longwangmiao Formations (Cambrian) possess strong exploration prospects for deep formations and abundant gas resources in the central basin. Deep fracture research has also attracted increasing attention, as it plays an important role in reservoir control. Previous studies have suggested a developed series of high- angle strike-slip fault systems in the central Sichuan Basin, but correlated exploration activities are limited, as distribution rules and dynamic mechanisms remain unclear. In this study, the geometric and kinematic characteristics of these strike-slip faults are described based on spectral decomposition coherence. Using comprehensive analysis technique of the strike-slip fault tectonic activity history, the formation and evolution processes of strike-slip faults and their control on hydrocarbon distribution were examined. The results showed that the deep strike-slip fault system, mostly distributed in the Dengying Formation, can be divided into four stages, three levels, and three groups of orientation, which controlled the structural framework and shape of the central Sichuan area, as well as the zoning from north to south, and blocking from west to east. The faults showed features of layered deformation and staged evolution in the vertical direction. The segmentation of strike-slip faults strongly controls the quality of fractured vuggy reservoirs. Reservoir of hard-linked zone of the strike-slip fault are the most developed， followed by that of soft-linked segments, and translational section of the strike-slip fault are relatively undeveloped. Strike-slip faults are important hydrocarbon migration paths, and their multistage activities have different controlling effects on hydrocarbon accumulation.